Development of competencies for participatory evaluation of sustainability and climate emergencies through the design of educational pathways - Leticia Concepción Velasco Martínez; Juan Jesús Martín Jaime; Juan Carlos Tójar Hurtado (Revista Española de Pedagogía)
In the context of the international climate emergency, it is essential to develop and research active and participatory learning initiatives in the university context that provide solutions based on environmental education for sustainability. This can be achieved through pedagogical approaches that integrate sustainability into the educational curriculum, with the aim of promoting the development of active, committed citizens. The main objective of this research is to promote the design of socio-educational pathways by groups of university students to help them learn to evaluate sustainability and climate emergencies in diverse contexts. The design of these paths should lead to active, participatory learning and the acquisition of competencies by the students. A mixed QUAL(quan) design was applied through a qualitative research workshop and a content analysis of the student-designed paths. The descriptive results show the profile and main characteristics of the paths designed. The qualitative analyses enabled the construction of comprehensive category systems and diagrams capable of explaining the relationships between the competencies developed and the proposals for improving sustainability on the university campus. The main conclusion is that designing environmental education paths plays a key role in helping groups of university students to learn about sustainability, to evaluate it and to come up with proposals for tackling the climate emergency on university campuses.